Analysis Of It-Based Logistics Inventory Systems In Companies Engaged In The Field Of Ready Mix Concrete And Precast Concrete - Pratama, Wiko; Wahyudi, Muhammad; Tanjung, Miftah Rusydi; Saputra, Risfan Nazar; Saragih, Juliyandri; Siregar, Andree Rizky Yuliansyah; Wijaya, Rian Farta (Cattleya Darmaya Fortuna, 2024)
This journal aims to analyze information technology (IT)-based logistics inventory systems in companies operating in the ready mix concrete and precast concrete fields. In the construction industry, efficient and accurate inventory management is critical to supporting effective and timely operations. This study identifies the problems existing in traditional inventory systems and proposes IT-based solutions to optimize logistics management. The methodology used includes needs analysis, system design, implementation, and system performance evaluation. The results of the research show that implementing an IT-based inventory system can increase the accuracy of inventory data, speed up the decision-making process, and reduce operational costs. This system also allows for better integration between various departments within the company, thereby improving overall coordination and efficiency. This study concludes that technological innovation in logistics management makes a significant contribution to increasing productivity and competitiveness of companies in the ready mix concrete and precast concrete industries.